2020
DOI: 10.1101/2020.05.14.20101691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Black/African American Communities are at Highest Risk of COVID-19: Spatial Modeling of New York City ZIP Code-Level Testing Results

Abstract: Introduction. The population and spatial characteristics of COVID-19 infections are poorly understood, but there is increasing evidence that in addition to individual clinical factors, demographic, socioeconomic and racial characteristics play an important role. Methods. We analyzed positive COVID-19 testing results counts within New York City ZIP Code Tabulation Areas (ZCTA) with Bayesian hierarchical Poisson spatial models using integrated nested Laplace approximations. Results. Spatial clustering accounted… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…These studies encouraged the formulation of environmental policies to control pollution sources, which can reduce the harmful effects of air pollutants. Studies from Li et al ( 2020 ) and DiMaggio et al ( 2020 ) showed that compared with the general population of the USA, black Americans were at apparently higher risk of COVID-19 infection and mortality nationwide. It is probably because black Americans suffer more from poverty, environmental pollution, overcrowded housing and less access to health care than do the general population of the USA.…”
Section: Discussionmentioning
confidence: 99%
“…These studies encouraged the formulation of environmental policies to control pollution sources, which can reduce the harmful effects of air pollutants. Studies from Li et al ( 2020 ) and DiMaggio et al ( 2020 ) showed that compared with the general population of the USA, black Americans were at apparently higher risk of COVID-19 infection and mortality nationwide. It is probably because black Americans suffer more from poverty, environmental pollution, overcrowded housing and less access to health care than do the general population of the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the risk among Asian children living in the United States is reduced ( Uehara and Belay, 2012 ), suggesting a role for environmental factors. Similarly, it is quite possible that environmental factors impact the ethnicity-based risk in MIS-C, as Black and Hispanic populations are more likely to be exposed to SARS-CoV2 ( DiMaggio et al, 2020 ; Vahidy et al, 2020 ). This factor is especially relevant at our hospital, and other metropolitan centers, which serve patients from diverse backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…This means that East Asians must be exhibiting significantly less susceptibility and/or transmissibility than people of other races. Only a few days back, a study has emerged [41] claiming that black people in New York City are more susceptible to infection than white people, so such racial factors might well be present here too. It had at one time been thought that the virus does not care about racial and national boundaries – that unfortunately doesn’t seem to be the case any longer.…”
Section: Implications Of the Mathematical Resultsmentioning
confidence: 99%